Ethnopharmacological study of natural products used for traditional cancer therapy in Algeria - Khaled Taïbi; Leila Ait Abderrahim; Karima Ferhat; Soria Betta; Fadhila Taïbi; Fatiha Bouraada; Mohamed Boussaid (Elsevier, 2020)
Traditional and complementary medicine constitutes an important, and often underestimated, source of healthcare for multiple diseases including cancer. However, little is known about the ethnomedical knowledge and practices in Northern Africa. The main objective of this study is to identify and analyze the variety of natural products used in Algerian ethnopharmacology for cancer therapy. For this purpose, semi-structured interviews with 225 traditional healers, herbalists and practitioners were realized in twelve locations in Algeria throughout field studies performed from June 2015 to July 2019. Interviews covered popular and vernacular names of the natural product, mode of use and administration, dose, period of treatment, toxicity and side effects among other data. The obtained results reveal the use of 113 medicinal plants (belonging to 53 families and 104 genera), 10 animal species and various products and by-products from different origins such as honey, olive oil, thorns, urine, milk, animal fat and the alkaline water of Zamzam. Basing on the frequency of citation (FC), use reports (UR) and use value (UV), the most used natural products for cancer treatment are honey (FC = 181, UR = 194, UV = 0.65), Nigella sativa L. (FC = 131, UR = 152, UV = 0.54), Aristolochia longa L. (FC = 118, UR = 144, UV = 0.51), Berberis vulgaris L. (FC = 111, UR = 142, UV = 0.51), Curcuma longa L. (FC = 107, UR = 121, UV = 0.43), Trigonella foenum-graecum L. (FC = 102; UR = 119, UV = 0.43), Citrus limon (L.) Obseck (FC = 97, UR = 120, UV = 0.43), Artemisia herba-alba Asso (FC = 92, UR = 115, UV = 0.41) and the holy water 'Zamzam' (FC = 110, UR = 110, UV = 0.43) respectively. Mixtures of two or more ingredients were frequently used. The use of Pelophylax saharicus skin' was reported for the first time for the treatment of visible tumors and skin cancer. This is the first study documenting the traditional uses of various natural products for cancer treatment in Algeria. Our findings are relevant to document the traditional uses of numerous natural products and to provide background basis to search for novel compounds for cancer therapy.